LOCUMENTS AND PERLOCUS ACTIONS IN THE NOVEL "KATA" BY NADHIFA ALLYA TSANA: (A SOCIOLINGUISTIC STUDY) - Siti Mutmainah Latifah; Ratna Dewi Kartikasari (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study examines the problem of locutionary and perlocutionary speech acts contained in the novel Kata by Nadhifa Allya Tsana (Rintik Sedu). This type of research is descriptive qualitative. The data collection technique used the free, involved conversation (SLBC) method. The data analysis technique used the determining element sorting method, a method whose determining tool was the speech contained in the novel Kata by Nadhifa Allya Tsana. The presentation of the results of data analysis uses the informal presentation method. The results of this research are locutionary speech acts, intentional effect perlocutionary speech acts, and accidental effect perlocutionary speech acts contained in the novel Kata by Nadhifa Allya Tsana. The locutionary speech acts contained in the novel Kata by Nadhifa Allya Tsana have five perlocutionary utterances that have an intentional effect and there are ten utterances that have an unintentional effect. It is called an intentional effect because the effect caused by the speech is in accordance with the intended speaker's intention. contained in the novel Kata there are eight speech data. The speech act perlocutionary effect contained in the novel Kata, there are two speech data. There are eight speech data of speech acts of intentional effect locution contained in the novel Kata. It is called an intentional effect because the effect caused by the speech is in accordance with the speaker's intention. It is called an unintentional effect because the effect caused by the speech is not in accordance with the speaker's intention. The effects caused by perlocutionary utterances have the intention of insinuating, wishing/wanting and influencing. Keywords:  speech acts, novels, sociolinguistics